2008
DOI: 10.2131/jts.33.525
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in protein binding and its effect on toxicokinetics (TK) / toxicodynamics (TD) of diclofenac and propranolol in pregnant rats

Abstract: -Plasma protein binding is an important factor for the kinetics of drugs and how they act composition, can affect drug binding and subsequent drug response. In the present study, we investigated the toxicokinetics (TK) and/or toxicodynamics (TD) of diclofenac and propranolol comparing pregnant Sparague-Dawley (SD) rats with non-pregnant SD rats in terms of protein binding and drug distribution.1 -acid glycoprotein (AGP), respectively. After a single administration of diclofenac, the area under plasma concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The genus Cissus has been widely used in traditional herbal medicine for the treatment of hemorrhoids, gastric ulcers and bone healing. Miida et al (2008) after a single administration of diclofenac, on observed the area under plasma concentration-time curve (AUC) based on free diclofenac in pregnant rats was 3.9 times higher than that in non-pregnant rats. This difference is due to a lower concentration of serum albumin and a higher concentration of non-esterified fatty acid (NEFA) that inhibits drug binding to albumin, in pregnant rats.…”
Section: Physical Development Parametersmentioning
confidence: 99%
“…The genus Cissus has been widely used in traditional herbal medicine for the treatment of hemorrhoids, gastric ulcers and bone healing. Miida et al (2008) after a single administration of diclofenac, on observed the area under plasma concentration-time curve (AUC) based on free diclofenac in pregnant rats was 3.9 times higher than that in non-pregnant rats. This difference is due to a lower concentration of serum albumin and a higher concentration of non-esterified fatty acid (NEFA) that inhibits drug binding to albumin, in pregnant rats.…”
Section: Physical Development Parametersmentioning
confidence: 99%
“…Hepatic metabolites of DIC are 4‐hydroxy DIC and other hydroxylated forms which are eliminated from the body through the urine (65%) and bile (35%) after glucuronidation and sulfation (Small, ; Vane & Botting, ). Nevertheless, DIC is associated with severe adverse effects in gastrointestinal, lung, hepatic, and renal tissues (Brater, ; Miida et al, ; Pourjafar & Derakhshanfar, ; Tomic et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…DIC is associated with severe adverse effects in gastrointestinal, lung, hepatic, and renal tissues (Brater, 2002;Miida et al, 2008;Pourjafar & Derakhshanfar, 2004;Tomic et al, 2008).…”
mentioning
confidence: 99%
“…The model was validated by evaluating the impact of increased AGP levels on propranolol, a drug known to have high binding affinity to AGP. 4,7,10,26,28,31,49 Ultimately, establishing this model will provide heightened visibility of the protein binding characteristics of drugs and yield more informed data interpretation.…”
mentioning
confidence: 99%